No Correlation Exists between Disease Activity and the Expression of Killer-Cell Immunoglobulin-Like Receptors in Patients with Rheumatoid Arthritis - Toshiaki Kogure; Takeshi Tatsumi; Atsushi Niizawa; Hiroshi Fujinaga; Tomoyuki Ito; Yutaka Shimada; Katsutoshi Terasawa (Hindawi Limited, 2007)
Objective. The genes for killer-cell immunoglobulin-like receptors (KIRs) have been cloned and their functions and expression in patients with rheumatoid arthritis (RA) have been partially clarified. However, the correlation between their expression and disease activity has not been analyzed in patients with RA. Thus, we measured KIR expression on lymphocytes in patients with RA, and assessed the correlation between KIR expression and disease activity. Patients and Methods. In the cross-sectional study, 15 patients (9 females and 6 males) who fulfilled the diagnostic criteria for RA were assessed. In the longitudinal study, patients who were followed-up for 3 months were assessed. CD158a/b expression on peripheral blood mononuclear cells (PBMC) of RA patients was analyzed using flow cytometry. Results. No significant correlation between KIR expression and CRP, ESR, or IgM-RF was observed. There was no remarkable change in the expression of KIRs between the baseline and after 3 months. Additionally, in the 5 patients whose expression of KIRs particularly changed, the time-related changes in the expression of KIRs were independent from those of inflammation parameters and IgM-RF. Conclusion. There was no correlation between KIR expression and disease activity; therefore, the clinical use of KIR expression should be limited, while unnatural KIR expression may be involved in the pathogenesis of RA, but not a recruitment of chronic inflammation to induce joint damage.